Controlled trial comparing two types of enteral nutrition in treatment of active Crohn's disease: elemental versus polymeric diet. Issue 12 (December 1991) - Rigaud, D; Cosnes, J; Le Quintrec, Y; René, E; Gendre, J P; Mignon, M
Abstract : To determine whether an elemental diet or a polymeric defined formula diet would be more effective for treating active Crohn's disease, we conducted a prospective randomised clinical trial in 30 patients with active Crohn's disease unresponsive to steroids and/or complicated by malnutrition. They received a four to six week enteral nutrition course with either an elemental diet or a polymeric diet. Clinical remission occurred in 10 of the 15 patients on elemental diet compared with 11 of the 15 patients assigned to polymeric diet. Both groups showed similar improvements in nutritional status, biological inflammation, alpha 1 antitrypsin clearance, and colonoscopic lesions (diminished in 17 out of 24 patients). Most patients relapsed during the year after discharge. We conclude that enteral nutrition, whatever the diet, is an efficient primary therapy for active Crohn's disease but does not influence the long term outcome.